Analysis of Occupational Safety and Health (OSH) Implementation and Child Accident Prevention Efforts in Early Childhood Education (PAUD) Environment in Ketanggungan District, Brebes, Central Java: Analisis Implementasi Keselamatan dan Kesehatan Kerja (K3) dalam Upaya Pencegahan Kecelakaan pada Anak di Lingkungan Pendidikan Anak Usia Dini Kecamatan Ketanggungan, Brebes,Jawa Tengah - Alda Dwi Rizki Aulia; Triana Srisantyorini; Nurfadhilah Nurfadhilah (Academia Open, 2025)
Background: Early childhood settings require structured safety provisions due to children’s physical vulnerability and limited hazard awareness. Specific background: Although regulations and formal procedures exist, the consistency of Occupational Safety and Health (OSH) practices varies across early childhood institutions. Knowledge gap: Limited research has examined differences in OSH practices based on accreditation levels within Early Childhood Education settings. Aims: This study analyzes OSH implementation and child accident prevention efforts in three institutions with different accreditation levels in Ketanggungan District, Brebes, Central Java. Results: Findings show incomplete and inconsistently applied procedures, inadequate facilities, limited teacher competence in safety practices, and reactive rather than preventive risk-control systems. Variations in OSH practices align with managerial capacity, resource availability, and cultural norms within each institution. Novelty: This study highlights disparities in OSH readiness across accreditation levels, offering a contextualized understanding of how structural and managerial conditions shape safety practices. Implications: Strengthening OSH implementation requires integrated procedures, routine training, structured risk management, and collaborative engagement among educators, parents, and school leaders to support safer and more sustainable learning environments. Highlights Variations in safety practices appear across institutions with different accreditation levels. Preventive measures remain limited due to insufficient procedures, facilities, and training. Strengthened collaboration among educators and parents supports safer learning environments. Keywords Occupational Safety And Health, Early Childhood Education, Accident Prevention, Safety Procedures, Learning Environment